Management of hospitalized patients during the COVID-19 pandemic: review (Research, Society and Development, 2022)
SARS-CoV-2 is the leading agent of the current pandemic and is the cause of severe acute respiratory syndrome. Thus, hospital procedures are considered factors of high risk of contamination, with a high possibility of causing viral spread, in addition to nosocomial contamination. This article was developed with the objective of presenting a review of the current protocols that aim to guide on the approach of patients with COVID-19, as well as the recommendations recommended in relation to aerosol-generating medical procedures. To this end, a study of narrative literature review was carried out. In order to prevent infections, as current recommendations recommend the mandatory use of masks, aprons, gloves and eye protection. Regarding orotraqueal intubation and mechanical ventilation, you should choose the most experienced doctor on the team and prefer “fast sequence intubation”. In the case of a tracheostomy, it must be performed following all the steps defined in the protocols. In relation to cardiopulmonary resuscitation, there must be five health professionals with functions very well applied and reviewed, according to the practices of maintenance, ventilation, medication administration and completion of resuscitation. Within the intensive care unit, it is necessary to assess the expandability of the location, such as the increase in the multidisciplinary team. During a pandemic, it is imperative that a risk-benefit assessment is carried out before indicating surgery. Therefore, it is evident that changes in world protocols are important for minimizing aerosols, offering greater safety to all involved, whether they are professionals or patients.